Effects of electron–phonon coupling on damage accumulation in molecular dynamics simulations of irradiated nickel. Issue 12 (2nd December 2019) - Zarkadoula, Eva; Samolyuk, German; Weber, William J.
ABSTRACT: The role of the electronic system in high energy displacement cascades is explored. The energy exchange between the electronic and the atomic subsystem is described by the electron–phonon coupling. The electronic effects on the damage accumulation due to 100 keV Ni ion cascades in nickel, a prototype system to a large group of nickel-based high entropy alloys, are investigated for overlapping cascades. It is shown that the energy exchange between the two subsystems affects microstructure evolution, resulting in the formation of smaller clusters and more isolated defects. This effect is more significant for the vacancy cluster formation and size distribution. IMPACT STATEMENT: The effect of electron–phonon coupling on the damage accumulation due to ion irradiation is investigated for the first time, with results showing significant effects on the vacancy cluster formation. GRAPHICAL ABSTRACT: